الأحكام القانونية المستحدثة في مجال الملكية الفكرية على ضوء إتفاقية تريبس - سمرود عبد القادر (My University, 2023)
ملخص عام تعتبر إتفاقية ترييس من أهم الإتفاقيات الدولية التي حظت باهتمام دولي من طرف الفاعلين على ستوى الإبداع والابتكار والتجارة الدولية، فجاءت بأحكام قانونية مشكلة من أحكام عامة وأحكام تفصيلية وحتى تكون أكثر فاعلية من الإتفاقيات الدولية التي سبقتها جاءت بقواعد قانونية تتعلق باليات وميكانيزمات إنفاذ وحماية حقوق الملكية الفكرية، ووضعت وسائل تسوية المنازعات المتعلقة بالقضايا المتصلة بها، إلا أنه أثرها على الدول النامية تراوح بين النفع والضرر بحكم سيطرة الدول المصنعة القوية على حساب الدول الضعيفة، فمواطن المرونة تجلت في التراخيص التعاقدية والإجبارية والإستنفاذ الدولي والاستيراد الموازي والهندسة العكسية، والفترات الإنتقالية المسموحة للدولة النامية، بينما مواطن الليونة فتمثلت في العقوبات الممكن توقيعها على الدول النامية في حالة الإخلال بالالتزامات التعاقدية، والتأثير السلمي على التنوع البيولوجي، والسطو على موارد الدول النامية دون الحصول على متطلباتها من دواء وغذاء بأسعار معقولة . الكلمات الدالة : الملكية الفكرية اتفاقية تريس المستحدث الأحكام القانونية الدول النامية الآثار المجالات الحيوية The TRIPS Agreement is considered one of the most important international agreements that attracted international attention from actors at the level of creativity innovation and international trade. It came with legal provisions composed of general provisions and detailed provisions, and in order to be more effective than the international agreements that preceded it, it came with legal provisions related to mechanisms and mechanisms for the enforcement and protection of property rights. Intellectual issues, and the means of settling disputes related to the issues related to it. However, Its impact on countries that are unable to industrialize ranges between benefit and harm due to the shong control of industrialized countries at the expense of weak countries. Flexibility points are manifested in contractual and compulsory licenses. intemational enforcement, parallel imports, and transitional periods allowed for a developing country. While the soft spots are represented in the penalties that can be imposed on countries that are unable to industrialize in case of breach of contractual obligations, the negative impact on biodiversity and the robbery of the resources of developing countries without obtaining their requirements of medicine and food at affor
Keywords: الملكية الفكرية اتفاقية تريس المستحدث الأحكام القانونية الدول النامية الآثار المجالات الحيوية